Editorial: Advancing Islamic economics: Integrating finance, empowerment, and technology for sustainable growth. - Hendryadi, Hendryadi (LPMP Imperium, 2024)
This editorial introduces a special issue dedicated to the operationalization of Islamic economic principles in the modern world. The collection of research presented herein explores the critical intersection of Sharia-compliant finance, strategic marketing, and community empowerment. Topics range from practical banking mechanisms—such as credit scoring systems and risk management for home financing—to broader socio-economic studies on empowering Micro, Small, and Medium Enterprises (MSMEs) and agricultural communities. The issue also addresses the pivotal role of digital technology and the halal lifestyle in attracting a new generation to Islamic banking. Collectively, these studies provide a comprehensive roadmap for building a resilient, ethical, and inclusive economic ecosystem grounded in Islamic values, demonstrating their relevance and application from individual consumer behavior to national economic sustainability.